(untitled) (Revista Iberoamericana de Estudios Municipales, 2022)
This article makes a proposal of job segments and profiles for the Maule region, Chile. It is a historically significant territory for the country, however, it maintains a backward labor structure in different aspects linked to the characteristics of its employer profiles, its fractions of self-employment and dependent activities. A characterization of the region’s labor market is then proposed, accounting not only for its territorial particularities, but also for the internal variability of the distribution of labor aggregates throughout the territory. To develop our typology of job segments and profiles, a methodology is applied that combines the techniques of correspondence analysis and the k-means cluster, resulting in a total of eight job groups that are representative of the labor reality in the region.